Is Africa’s growing public debt really crowding out private investment? - Mulangu, Francis (2020)
Total external debt for sub-Saharan Africa jumped nearly 150% to $583 billion in 2018, from $236 billion 10 years earlier according to the World Bank. Many now worry the debt burden is unsustainable. Average public debt increased from 2010-2018 by 40%, and now stands at 59% of GDP. Whether debt levels are rising is not the real issue. The main concern should be on whether the returns on public investment exceed the interest rates paid on the loans that fund them. Commentators argue that the loans finance infrastructure projects with returns only in the distant future, compared to the medium term nature of the loan interest payments. The case of the Nairobi-Mombassa rail project in Kenya is often pointed as a prime example of the mismatch. The incongruity between the timing of the cost of servicing the loans and the returns on the public investment they are used for will cause budget deficits because governments will not be able to meet their expenditure commitments by only using revenues and grants. This will prompt African governments to use Treasury bill to fund part of the national budget with loans from domestic commercial banks, a practice that may crowd out private sector investment. To decide whether public debt in Africa is crowding out private investment, we must answer three questions. One, are African debts being productively used? We will use IMF projections of public debt and economic growth across countries to answer this question. Do stronger institutions and a better business environment accompany the accumulation of debt? The answer will inform us whether investors agree that Africa truly has investment potentials that justify large scale infrastructure investment, versus investors responding mainly to higher interest rates. Third, do African firms rely on commercial banks to support both their working capital expenditures and long-term investment? Moreover, how has this changed over the period during which national debts have been rising? We will investigate this question by using evidence from firm level data collected across more than 30,000 firms over 42 African countries between 2006 and 2019.